Cognitive governance, cognitive mapping and cognitive conflicts: Structural analysis with the MICMAC method - Garoui Nassreddine; Jarboui Anis (Cogent Economics & Finance, 2014)
This research aims to achieve a better understanding of the modes of conceptualization and thinking on issues of governance. It is part of a cognitive approach, to our knowledge unprecedented. This research has shown that the mapping concepts of governance can provide the original performance and meaningful. The purpose was to plot the thought of governance actors in the form of a cognitive map and analyze it. The results highlighted the relative importance of the concepts they used, the dimensions from which they structured more or less consciously, here own thoughts, and the nature and characteristics of the concepts they considered primarily as an explanation or consequences. They allowed characterizing very special or very precise structure and content of the thought of these actors. The construction of collective cognitive maps is to help structure the relationship between governance actors in the sense that it will detect the conflict relations of cognitive order. The cognitive map is by definition a representation of mental models of actors on any topic. Actors of governance do not have the same definitions of the concepts of governance that represents for us a sort of cognitive conflict and hence through cognitive mapping can map the concentration of these conflicts and we are still looking for more to show the effectiveness governance mechanisms to resolve these conflicts.
Keywords: A10; C00; D81; 330; cognitive map; governance cognitive; cognitive conflicts